Dietary Pharmacological Zinc and Copper Enhances Voluntary Feed Intake of Nursery Pigs - De Mille, Carson M.; Burrough, Eric R.; Kerr, Brian J.; Schweer, Wesley P.; Gabler, Nicholas K. (Frontiers in Animal Science, 2022)
The objective of the three experiments herein were to characterize the effect of pharmacological zinc and copper concentrations on nursery pig feed intake, stomach ghrelin, energy and nutrient digestibility, and mineral retention in post-weaned pigs. In Expt. 1, 300 weaned pigs were allotted across three dietary treatments (n = 10 pens/treatment) and fed in two diet phases (P1 and P2) lasting 7 and 14 days, respectively. Treatments were: 1) Control diet with no pharmacological minerals in P1 and P2, CON; 2) CON + 3,000 mg/kg Zn and 200 mg/kg Cu (P1), no pharmacological minerals in P2, ZC-CON; and 3) CON + 3,000 mg/kg Zn and 200 mg/kg Cu (P1), CON + 2,000 mg/kg Zn and 200 mg/kg Cu (P2); ZC). Over the 21-day test period, ZC pigs had 15% higher ADG and 13-24% ADFI compared to the CON and ZC-CON pigs (P < 0.05). Compared to the CON, ZC-CON and ZC pig daily feed intakes were 29% and 73% higher by day 5 and 7 post-weaning, respectively, compared to the CON pigs (P < 0.0001). However, removing pharmacological minerals in P2 abruptly decreased ZC-CON daily feed intake within 24 hours to similar intakes as the CON compared to the ZC pigs (0.17, 0.14 and 0.22 kg/d, respectively, P < 0.05). Dietary pharmacological minerals increased stomach fundus ghrelin-positive cells than CON pigs at day 7 (P = 0.005) and day 21 (P < 0.001). However, fasting plasma total and acyl-ghrelin concentrations did not differ from a control in response to zinc oxide daily drenching (Expt. 2). Expt. 3 showed that zinc and copper to have moderate to low retention; however, pharmacological zinc and copper diets increased zinc (P < 0.05) and copper retention (P = 0.06) after 28 days post-weaning compared to control pigs. Pharmacological zinc and copper did not improve DE, ME or nitrogen balance. Altogether, dietary pharmacological zinc and copper concentrations improve growth rates and mineral retention in nursery pigs. This improved performance may partially be explained by increased stomach ghrelin abundance and enhanced early feed intake in newly weaned pigs fed pharmacological concentrations of zinc and copper.